Optimizing The Focus of Children with Mental Disabilities Through Fishing Game: Optimalisasi Fokus Anak Tunagrahita Melalui Permainan Memancing Ikan - Adawiyah Harahap, Yuliatil; Sharfina, Dirayati; Leini Saragih, Srimis; Hati, Yulis; Chandra, Putra; Muchsin, Rosanti (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Yayasan Rumah Ceria Medan is an inclusive school located in Medan City. This school includes a preschool, kindergarten, and elementary school, with 16 children with special needs. Children with special needs face various problems, especially when participating in learning activities at school. One of them is the problem of focusing on learning. Children with intellectual disabilities are children who have problems focusing on learning. Playing is one of the important activities for children with intellectual disabilities because playing is a repetitive activity for pleasure and satisfaction. Fishing games are an educational game tool (APE) that is constructive and fun. The main function of fishing games in general is as a means to train children in understanding instructions given by the teacher, but specifically fishing games can be used to train children's focus. This activity aims to carry out fishing games as an activity to optimize focus for children with intellectual disabilities at Yayasan Rumah Ceria Medan. The steps of the activity consist of: 1) Introduction with a time of 5 minutes. 2) Core activities for 20 minutes. 3) Closing with a time of 5 minutes. After completing the activity, the educator evaluates the results of observations obtained during the game. Results: 1) Fishing games can improve the focus of children with intellectual disabilities, 2) Fishing game activities are used as routine therapy to improve the focus of children with intellectual disabilities, and 3) This activity is expected to be applicable to other children's conditions, including children with autism and ADHD.